2014 Underwater Communications and Networking (UComms) 2014
DOI: 10.1109/ucomms.2014.7017148
|View full text |Cite
|
Sign up to set email alerts
|

A parametric replay-based framework for underwater acoustic communication channel simulation

Abstract: This paper lays the foundation of an underwater acoustic channel simulation methodology that is halfway between parametric modeling and stochastic replay of at-sea measurements of channel impulse responses. The motivation behind this approach is to extend the scope of use of replay-based methods by allowing some parameterization of the channel properties while complying with some level of realism. Based on a relative entropy minimization between the original channel impulse response and the simulated one, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The Doppler frequency shift in the received signals was removed as described in [14]. The temporal coherence of channels at different receiving depths was then calculated using Equation (7). The temporal coherence results at different receiving depths are shown in Figure 15.…”
Section: Channel Temporal Coherence and Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Doppler frequency shift in the received signals was removed as described in [14]. The temporal coherence of channels at different receiving depths was then calculated using Equation (7). The temporal coherence results at different receiving depths are shown in Figure 15.…”
Section: Channel Temporal Coherence and Cluster Analysismentioning
confidence: 99%
“…Previous studies have focused on three characteristic channel parameters: amplitude, delay spread, and channel temporal coherence. As a basis for statistical channel modeling, the distribution of the envelope amplitude has been fitted to Rayleigh distribution [5][6][7], Rice distribution [8][9][10][11], lognormal distribution [12,13], K distribution [14,15], and Burr distribution [16]. Most of these studies analyze specific experimental data for statistical modeling of channel amplitudes and fading, providing references for channel prediction and channel tracking.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted to design a stochastic UWA channel model [17][18][19][20][21][22][23][24][25][26][27][28] based on the assessment of the experimental acoustic data retrieved at certain specific locations. Authors have suggested Ricean fading [17,18] or Rayleigh fading [19][20][21], however, in some works, log-normal distribution [22,23] and the Ricean shadowed distribution [26] to enable better fit for measurement. The majority of these approaches apply experiment-specific characteristics, including location of the network deployment and the kind of signals to be applied to perform the test.…”
Section: Channel Modementioning
confidence: 99%
“…A preliminary version of this paper has been presented at the Conference on Underwater Communications and Networking (UComms) held in Sestri Levante, Italy, in September 2014 [1]. DRAFT conduct.…”
Section: Introductionmentioning
confidence: 99%
“…stochastic replay). 1 From a single measurement, it is thus possible to compare competing transmission schemes when faced with the same realistic environment [5]. Thanks to Monte-Carlo simulations, design and validation metrics such as bit error rate [3]- [5], capacity bounds [6]- [8] or fading statistics [4] can be computed with a good accuracy.…”
Section: Introductionmentioning
confidence: 99%